2012
DOI: 10.1016/j.jvs.2012.03.259
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endovascular treatment of traumatic aortic transection

Abstract: Endovascular repair allows rapid and minimally invasive therapy in patients with traumatic aortic injury with good technical results. The outcome is highly dependent on the severity of other concurrent injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…13,15,17 This poses several technical and logistical challenges as young patients tend to have a more acute curvature of the aortic arch with the risk of poor apposition of the stentgraft, thereby a tendency to develop a bird beak configuration with an increased risk of subsequent endoleak and stent graft collapse. 1,11 In the present cohort, five of the 13 patients who underwent reintervention had infolding and partial stent graft collapse; in three of them it occurred within 3 weeks of the acute TEVAR. Plausibly, some of the re-interventions related to oversizing could have been avoided if more suitably sized stent grafts had been obtainable.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13,15,17 This poses several technical and logistical challenges as young patients tend to have a more acute curvature of the aortic arch with the risk of poor apposition of the stentgraft, thereby a tendency to develop a bird beak configuration with an increased risk of subsequent endoleak and stent graft collapse. 1,11 In the present cohort, five of the 13 patients who underwent reintervention had infolding and partial stent graft collapse; in three of them it occurred within 3 weeks of the acute TEVAR. Plausibly, some of the re-interventions related to oversizing could have been avoided if more suitably sized stent grafts had been obtainable.…”
Section: Discussionmentioning
confidence: 71%
“…All four centers followed the same patient management principles and had 24/7 on call systems with readiness to perform TEVAR around the clock. The Uppsala protocol for trauma patients with blunt aortic injury has been reported previously, 11 and so has an early Zurich series of patients. 12 The patients were monitored by CT angiography before discharge and at 1 month, after 3e6 months, and at 12 months, and annually thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…20 Comparisons between age, ISS score, GCS score, and outcome in patients who did and did not receive heparin at the time of endovascular stenting did not reveal any significant differences, but our sample size is too small for definitive conclusions on this subject. Of the 7 patients who received heparin, 6 did not experience progression of their intracranial lesions, and 1 died of hemodynamic instability prior to repeat imaging.…”
Section: Anticoagulation Therapy In Aortic Injury/tbimentioning
confidence: 66%
“…3 However, open thoracic aortic surgery often requires a thoracotomy with single-lung ventilation and aortic cross-clamping, which can have severe, negative consequences in polytrauma patients, including a surge in mean arterial blood pressure and cerebral circulation. 6,20 The on ly case series we found that specifically addresses treatment of aortic injury with TBI suggested that only endovascular procedures and conservative management should be used if TBI is present. 13 However, Mosquera et al found that with conservative, nonoperative treatment, 38% of patients experienced a complication that resulted in death or required a delayed operative intervention after discharge from the hospital.…”
Section: Hospital Managementmentioning
confidence: 99%
“…Endovascular aortic repair (EVAR) improves clinical outcomes, as evidenced by reduced operative morbidity and mortality and shorter hospital stays. Thus, this procedure has become the preferred option for treatment of several aortic pathologies, such as aortic dissection, aneurysms and ruptured aneurysms, and traumatic injury, during the past decade [ 1 6 ]. The common femoral artery must be exposed during conventional endovascular repair, and this surgical cutdown (SC) technique increases the incidence of complications associated with the incision [ 7 ].…”
Section: Introductionmentioning
confidence: 99%